Effect of apple pomace silage on blood parameters in Suffolk ewe: Apple pomace silage in ewes (Bangladesh Journal of Animal Science, 2018)
The experiment was carried out to assess the effects of feeding apple pomace silage (APS) on blood parameters in Suffolk ewes. Three ewes were used in 3×3 Latin square design over three periods with three dietary treatments as hay diet, low ethanol APS (L-APS, ethanol 48.7 g kg-1 DM) diet and high ethanol APS (H-APS, ethanol 87.2 g kg-1 DM) diet. Alfalfa hay cube and APS provided half of 110% TDN requirement for APS diets. The area upper or under the curve (AUC) of plasma ethanol was greater (P